The prion-ZIP connection: From cousins to partners in iron uptake - Singh, Neena (Prion, 2015)
Converging observations from disparate lines of inquiry are beginning to clarify the cause of brain iron dyshomeostasis in sporadic Creutzfeldt-Jakob disease (sCJD), a neurodegenerative condition associated with the conversion of prion protein (PrP(C)), a plasma membrane glycoprotein, from α-helical to a β-sheet rich PrP-scrapie (PrP(Sc)) isoform. Biochemical evidence indicates that PrP(C) facilitates cellular iron uptake by functioning as a membrane-bound ferrireductase (FR), an activity necessary for the transport of iron across biological membranes through metal transporters. An entirely different experimental approach reveals an evolutionary link between PrP(C) and the Zrt, Irt-like protein (ZIP) family, a group of proteins involved in the transport of zinc, iron, and manganese across the plasma membrane. Close physical proximity of PrP(C) with certain members of the ZIP family on the plasma membrane and increased uptake of extracellular iron by cells that co-express PrP(C) and ZIP14 suggest that PrP(C) functions as a FR partner for certain members of this family. The connection between PrP(C) and ZIP proteins therefore extends beyond common ancestry to that of functional cooperation. Here, we summarize evidence supporting the facilitative role of PrP(C) in cellular iron uptake, and implications of this activity on iron metabolism in sCJD brains.